Analysis of Student Participation Pursuing Package C in Online Learning During the Covid-19 Pandemic - Artha, I Ketut Atmaja Johny; Widodo, Widodo; Nusantara, Widya; Cahyani, Arini Dwi (Journal of Nonformal Education, 2022)
The Covid-19 pandemic has limited public service activities, including education. Package C education at CLC has diverse student backgrounds, so educators must make online learning by conducive. The purpose of this study was to describe the level of participation of students pursuing package C in online learning during the Covid-19 pandemic at CLC Cerme Gresik. This study uses quantitative research with a survey approach. The sampling technique used was purposive sampling with a total of 35 students pursuing package C. Data collection techniques using questionnaires were carried out online using "WhatsApp.". The data analysis technique of this research used descriptive statistical techniques. The study results are by the data on the percentage of student participation rates pursuing package C in online learning during the Covid-19 pandemic at CLC Cerme Gresik, 82.5%. Learning through online learning is one of the current alternatives to continue to carry out the teaching and learning process. Students' enthusiasm in participating in package C at SKB Cerme Gresik during online learning can be seen from several aspects of participation, which include 1) Student attendance, 2) Discussion participation, 3) Completing assignments, 4) Question and answer participation, 5) taking notes on teacher explanations, 6 ) conclude at the end of the lesson and 7) determine the results of the evaluation. During online learning, there are cognitive, affective, and psychomotor changes for students. Judging from the changes during online learning, namely 1) fostering the spirit of learning, 2) Literacy towards technology, 3) Interpersonal interaction skills, 4) Collaboration and 5) Independent learning skills.